PERAN GURU TERHADAP KETERLIBATAN SISWA TUNARUNGU DI SLB TPI AMPLAS - Fitria Rhamadona; Nadia Azlila; Manda Azzahra; Fathun Najah Sr; Ramadhani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the role of teachers in increasing the engagement of deaf students during the learning process at the TPI Amplas Special Needs School (SLB). Student engagement is a crucial factor supporting successful learning, encompassing behavioral, emotional, and cognitive aspects. This study employed a quantitative descriptive method involving one teacher and six deaf students as research subjects. Data collection was conducted through questionnaires, observation, and documentation. The research instrument was developed based on indicators of teacher roles, such as classroom management, use of learning media, motivation, use of sign language, and the ability to build effective learning interactions. Student engagement was measured through indicators of attention during learning, participation in learning activities, task completion, learning motivation, and comfort during learning. The results of the study indicate that teachers play a positive role in increasing the engagement of deaf students. This is evident in the use of visual media, sign language, concrete examples, and consistent motivation throughout the learning process. Furthermore, teachers are able to create a comfortable and conducive learning environment, thus increasing student enthusiasm for learning activities. Based on the questionnaire results, the majority of students showed good attention to teacher explanations, actively participated in learning activities, and made an effort to understand the material presented. However, some students were still reluctant to ask questions and occasionally experienced boredom during the lesson. Therefore, it can be concluded that the role of teachers significantly contributes to the engagement of deaf students in learning. The more effective the strategies implemented by teachers, the higher the students' participation and engagement in the learning process.